PARTISIPASI POLITIK MASYARAKAT DALAM PEMILIHAN KEPALA DAERAH SERENTAK TAHUN 2020 DI KECAMATAN LONG BAGUN KABUPATEN MAHAKAM ULU - Kelawing Bayau Juleha (Jurnal Paradigma (JP), 2022)
This study aimed to describe and analyze Community Political Participation in the Election of Regent and Deputy Regent of Mahakam Ulu Regency for the Period 2020 – 2024 in Long Bagun District, Mahakam Ulu Regency. This research is a combination or mixed-method analysis, by conducting structured interviews with the organizers and conducting a survey of the community by taking the probability method using a precision of 10%. The study results concluded that public political participation in dialogues/debates was still low due to mass mobilization during the Covid-19 pandemic. The people's political involvement in direct political campaigns is also still low, and only a tiny part is followed by the people who become the success team or become part of the supporting party that participates in this political campaign. However, community involvement in campaigns through social media is good by joining the Instagram and Facebook social media networks belonging to the Mahakam Ulu Regency KPU. Then, the public's political participation in using the right to vote, in general, is pretty high.